Banking and Sovereign Risk in the euro area - Stefan Gerlach; Alexander Schulz; Guntram B. Wolff (Verein für Socialpolitik, 2010)
We study the determinants of bond spreads of euro area sovereigns since the introduction of the euro. We show that an aggregate risk factor is a main driver of spreads. The aggregate risk factor also plays an important role for sovereign risk through its interaction with the size and structure of national banking sectors. When the aggregate risk factor increases, countries with large banking sectors and low equity ratios of the banking sector will see their yield spreads raise. Global risk-aversion hikes can therefore turn a banking sector into a systemically relevant risk to governments that can be measured in sovereign spreads. Government debt levels and forecasts of future fiscal deficits are also significant determinants of sovereign spreads.
Keywords: E43; E44; G12; 330; sovereign bond markets; banking; liquidity; EMU